A polysaccharide oil-proof lightweight wrapping paper base material and a preparation method thereof

CN122880032APending Publication Date: 2026-10-09ZHEJIANG HENGDA NEW MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611025131.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-10
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0003]针对现有技术中天然多糖防油涂层需要高涂布量才能实现致密阻隔且涂层与纸基之间因依赖物理吸附而结合不牢固的不足,本申请提供了一种多糖防油轻量包装纸基材料及其制备方法

Benefits of technology

[0019]通过在纸浆纤维表面构建疏水性交联网络作为底层预阻隔结构,该交联网络封堵纤维间毛细管通道并降低纤维亲水性,使得油脂无法通过纤维网络进行侧向扩散渗透,从而降低了表面多糖涂层的致密性要求。同时,所述交联网络中保留的残余活性基团与表面涂布的含氨基天然多糖之间发生化学锚固反应,形成共价键连接,使涂层与纸基之间的结合力从物理吸附提升为化学键合,在油脂浸润和湿态条件下仍能保持界面结构完整。底层预阻隔与表面致密膜的功能耦合使得表面涂层无需独立承担全部阻隔压力,在低涂布量条件下即可实现连续无孔的防油阻隔效果,兼顾了纸基材料的轻量化和经济性。此外,所述制备方法全部采用天然可再生多糖原料,所得包装纸基材料可完全回收再利用。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122880032A_ABST
    Figure CN122880032A_ABST
Patent Text Reader

Abstract

The application provides a polysaccharide oil-proof lightweight packaging paper base material and a preparation method thereof. The preparation method comprises the following steps: performing in-pulp crosslinking treatment on pulp fibers to form a hydrophobic crosslinking network containing residual active groups on the surface of the fibers, and obtaining modified pulp; the modified pulp is formed into a paper base; an oil-proof coating liquid mainly containing amino-containing natural polysaccharides is prepared; the coating liquid is applied to the surface of the paper base, the amino groups of the polysaccharide molecules in the coating liquid react with the residual active groups of the crosslinking network on the surface of the paper base fibers to form chemical anchoring, and the polysaccharide oil-proof lightweight packaging paper base material is obtained. The hydrophobic crosslinking network in the paper base layer blocks the capillary channel between the fibers to form a bottom layer pre-blocking structure, and the surface polysaccharide coating layer is covalently bonded to the paper base through chemical anchoring, and the synergistic effect of the two layers can realize continuous and non-porous oil-proof blocking effect under the condition of low coating amount, and the lightweight and coating layer firmness are considered.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of food packaging materials technology, specifically to a polysaccharide oil-resistant lightweight packaging paper-based material and its preparation method. Background Technology

[0002] Food packaging paper-based materials need to possess effective oil-repellent properties to prevent grease from penetrating and contaminating food or outer packaging. Existing oil-repellent solutions mainly include two technical routes: fluorinated compound coating and polyolefin lamination. The former faces increasingly stringent environmental regulations and poses a risk of bioaccumulation, while the latter makes the paper-based material non-recyclable. While natural polysaccharide-based oil-repellent coatings can address environmental concerns, achieving a continuous, non-porous, and dense barrier effect with a single polysaccharide coating requires a high coating weight, leading to increased paper weight and cost, contradicting the need for lightweighting. Furthermore, the bonding between the natural polysaccharide coating and the untreated paper base relies primarily on physical adsorption, making it prone to interfacial delamination failure under grease-infiltrated or wet conditions, affecting long-term reliability. Summary of the Invention

[0003] To address the shortcomings of existing technologies where natural polysaccharide oil-repellent coatings require high coating amounts to achieve dense barrier properties and exhibit weak bonding between the coating and paper substrate due to reliance on physical adsorption, this application provides a polysaccharide oil-repellent lightweight packaging paper substrate material and its preparation method. This method constructs a hydrophobic cross-linked network containing residual active groups within the pulp fibers and utilizes the chemical anchoring reaction between these residual active groups and the surface-coated amino-containing natural polysaccharides to achieve functional coupling between the in-pulp pre-barrier layer and the surface polysaccharide film layer. This enables covalent bonding between the coating and the paper substrate and a synergistic oil-repellent effect under low coating amounts. Specifically, this application provides the following technical solutions:

[0004] In a first aspect, this application provides a method for preparing a polysaccharide-based oil-resistant lightweight packaging paper material, comprising:

[0005] Pulp fibers are subjected to intra-pulp crosslinking treatment to form a hydrophobic crosslinking network containing residual active groups on the surface of the pulp fibers, thereby obtaining a modified pulp.

[0006] The modified slurry is then formed into a paper base.

[0007] Prepare an oil-resistant coating solution based on amino-containing natural polysaccharides;

[0008] The oil-resistant coating liquid is applied to the surface of the paper base. The amino groups of the polysaccharide molecules in the oil-resistant coating liquid react with the residual active groups of the cross-linked network on the surface of the paper base fiber to form a chemical anchor, thereby obtaining a polysaccharide oil-resistant lightweight packaging paper base material.

[0009] Optionally, the intrapulp crosslinking treatment includes: sequentially adding cationic modified starch and a wet strength agent to the pulp fiber, wherein the cationic modified starch is adsorbed on the fiber surface to provide polyhydroxy reaction sites, and the wet strength agent contains nitrogen heterocyclic active groups, wherein the nitrogen heterocyclic active groups react with the polyhydroxy reaction sites and cellulose hydroxyl groups to form the hydrophobic crosslinking network.

[0010] Optionally, the wet strength agent is a polyamide polyamine epichlorohydrin resin, and the nitrogen heterocyclic active group is a aziridine group.

[0011] Optionally, the oil-resistant coating liquid further comprises nanocellulose and carboxyl-containing natural polysaccharides, wherein the amino-containing natural polysaccharides and the carboxyl-containing natural polysaccharides form an ionic cross-linked pre-assembled structure through electrostatic interactions between the amino and carboxyl groups.

[0012] Optionally, the amino-containing natural polysaccharide is chitosan, the nanocellulose is cellulose nanofibers, and the carboxyl-containing natural polysaccharide is sodium alginate.

[0013] Optionally, the process further includes a gradient temperature drying and curing treatment on the coated paper base, so that the hydrophobic crosslinking network is thermally cured and the polysaccharide coating on the surface of the paper base is densified to form a continuous non-porous barrier film.

[0014] Optionally, the reaction conditions for the intraslurry crosslinking treatment are: slurry pH value of 7.0 to 8.5, reaction temperature of 40 to 60 degrees Celsius, and stirring time of not less than 15 minutes.

[0015] Secondly, this application provides a polysaccharide-based oil-resistant lightweight packaging paper material, comprising a paper base layer and a polysaccharide oil-resistant barrier layer disposed on the surface of the paper base layer; the fiber surface of the paper base layer is distributed with a hydrophobic cross-linked network containing residual active groups; the polysaccharide oil-resistant barrier layer is mainly composed of amino-containing natural polysaccharides; the amino groups of the polysaccharide molecules in the polysaccharide oil-resistant barrier layer are chemically bonded to the residual active groups of the hydrophobic cross-linked network to form an anchoring connection.

[0016] Optionally, the hydrophobic crosslinking network is a network product formed by the crosslinking reaction of hydroxyl groups and aziridine groups of cationic modified starch and polyamide polyamine epichlorohydrin resin.

[0017] Optionally, the basis weight of the paper base layer is 40 to 60 grams per square meter, and the coating amount of the polysaccharide oil-resistant barrier layer is 2 to 3 grams per square meter.

[0018] The polysaccharide-based oil-resistant lightweight packaging paper material and its preparation method provided in this application have the following beneficial effects:

[0019] By constructing a hydrophobic cross-linked network on the surface of pulp fibers as a bottom-layer pre-barrier structure, this cross-linked network blocks the capillary channels between fibers and reduces the hydrophilicity of the fibers, preventing grease from laterally diffusing and penetrating through the fiber network, thereby reducing the density requirements of the surface polysaccharide coating. Simultaneously, the residual active groups retained in the cross-linked network undergo a chemical anchoring reaction with the amino-containing natural polysaccharides coated on the surface, forming covalent bonds. This upgrades the bonding force between the coating and the paper substrate from physical adsorption to chemical bonding, maintaining the integrity of the interface structure even under grease wetting and wet conditions. The functional coupling between the bottom-layer pre-barrier and the surface dense film means that the surface coating does not need to independently bear the entire barrier pressure, achieving a continuous, non-porous oil-resistant barrier effect even with low coating amounts, while also considering the lightweight and economical nature of the paper substrate material. Furthermore, the preparation method uses all natural and renewable polysaccharide raw materials, and the resulting packaging paper substrate material is fully recyclable. Attached Figure Description

[0020] Figure 1 This is a schematic diagram of the overall process for preparing polysaccharide oil-resistant lightweight packaging paper-based material according to an embodiment of this application.

[0021] Figure 2 This is a schematic diagram of the subprocess of intra-slurry crosslinking modification provided in an embodiment of this application.

[0022] Figure 3 This is a schematic diagram of the sub-process for preparing the ternary polysaccharide sizing solution provided in an embodiment of this application.

[0023] Figure 4 This is a schematic diagram of the surface coating and chemical anchoring process provided in the embodiments of this application.

[0024] Figure 5 This is a schematic cross-sectional view of a double-layer paper-based material structure provided in an embodiment of this application.

[0025] Figure 6 This is a schematic diagram of the chemical anchoring reaction mechanism provided in the embodiments of this application.

[0026] Figure 7 This is a schematic diagram of the gradient drying and curing sub-process provided in the embodiments of this application.

[0027] Figure 8 This is a schematic diagram of the module architecture of the polysaccharide oil-resistant lightweight packaging paper-based material preparation system provided in the embodiments of this application.

[0028] Figure 9 The drying kinetics curve of the polysaccharide coating provided in the embodiments of this application.

[0029] Figure 10 The thermosetting kinetics curve of polyamide polyamine epichlorohydrin resin provided in the embodiments of this application.

[0030] Figure 11 The diagram showing the relationship between coating drying stress and critical crack thickness is provided for an embodiment of this application.

[0031] Figure 12 The rheological property curve of the coating liquid provided in the embodiments of this application is shown.

[0032] Figure 13 The graph shows the relationship between the charge ratio of chitosan and sodium alginate and pH, as provided in the embodiments of this application.

[0033] Figure 14 This is a graph showing the relationship between coating amount and oil-resistant performance parameters provided in the embodiments of this application. Detailed Implementation

[0034] To make the objectives, technical solutions, and advantages of this application clearer, the technical solutions of this application will be clearly and completely described below in conjunction with the accompanying drawings and specific embodiments. Obviously, the described embodiments are only a part of the embodiments of this application, and not all of them. Based on the embodiments in this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application.

[0035] Furthermore, the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include one or more of that feature. In the description of this application, "multiple" means two or more, unless otherwise explicitly specified.

[0036] The polysaccharide oil-resistant lightweight packaging paper-based material and its preparation method provided in this application can be applied to various scenarios in the food packaging field, including fast food packaging paper, baking paper, takeaway food box liner paper, pastry tray paper, and other paper-based packaging products requiring oil-resistant barrier properties. The preparation method is applicable to papermaking production lines using wood pulp as raw material. The process can be integrated into existing paper machine equipment by adding an in-pulp modification unit and a surface coating unit, or offline coating can be performed on pre-made base paper on a separate coating processing line. The application equipment for the paper-based material includes, but is not limited to, papermaking equipment such as long-wire paper machines, double-wire paper machines, and rotary paper machines, as well as surface treatment equipment such as sizing press coating machines, doctor blade coating machines, and air knife coating machines.

[0037] In the field of paper-based materials for food packaging, existing oil-resistant technologies mainly include fluorinated compound coating and polyolefin lamination. Fluorinated compound coating faces increasingly stringent environmental regulations globally, and perfluorinated and polyfluoroalkyl substances pose a risk of bioaccumulation. Polyolefin lamination renders paper-based materials unrecyclable, contradicting the development direction of a circular economy. While natural polysaccharide oil-resistant coatings can address these environmental issues, in existing technologies, a single polysaccharide coating independently performs all oil-resistant barrier functions, requiring a high coating weight to form a completely dense, non-porous, continuous film, resulting in a significant increase in paper weight. Therefore, this application provides a method for preparing paper-based materials that achieves highly efficient oil-resistant barrier properties under low coating weight conditions through functional coupling of intra-pulp crosslinking pretreatment and surface polysaccharide coating.

[0038] The preparation method of the polysaccharide oil-resistant lightweight packaging paper-based material provided in this embodiment is implemented on a papermaking system with in-pulp modification function. The papermaking system includes a pulping unit, an in-pulp crosslinking modification unit, a paper forming unit, a coating solution preparation unit, a surface coating unit, and a drying and curing unit. The units are connected sequentially through pulp pipelines and a paper web transport system.

[0039] like Figure 1 As shown, the preparation method of the polysaccharide oil-resistant lightweight packaging paper-based material provided in this embodiment includes the following steps:

[0040] S000 involves preparing and beating the pulp raw materials to obtain a pulp suspension that meets the requirements for subsequent intra-pulp crosslinking modification.

[0041] The pulping process uses softwood pulp board and hardwood pulp board as raw materials, and mixes them at a mass ratio of 4:6. The softwood pulp fibers have an average length of 2.5 to 3.5 mm, providing skeletal strength and tear resistance for the paper sheet; the hardwood pulp fibers have an average length of 0.8 to 1.2 mm, filling the gaps between fibers to improve paper surface uniformity and smoothness, providing a basis for the uniformity of subsequent surface coating.

[0042] Softwood and hardwood pulp boards are separately fed into a hydrapulper, and process water is added. The pulp is broken down at room temperature for 20 to 30 minutes to completely dissociate the pulp into individual fibers. The pulp concentration after pulping is 4 to 5 wt%. The pulp is then screened using a pressure screen with a sieve opening width of 0.2 to 0.3 mm to remove undissociated pulp clumps and impurities, obtaining pure pulp. The screened softwood and hardwood pulps are then mixed evenly in a mixing tank at a mass ratio of 4:6.

[0043] The mixed pulp is fed into a disc refiner for beating, employing a semi-free, semi-viscous beating method. This semi-free, semi-viscous beating method refers to adjusting the disc gap to achieve both appropriate internal and external fiberization, increasing the interfiber bonding area, while retaining sufficient fiber length and stiffness to maintain the paper sheet's structural support. The beating specific pressure is controlled at 2.0 to 3.0 N / mm, and the beating concentration is 3 to 5 wt%. The beating endpoint, measured by the Schopper-Riegler method, reaches a freeness of 38%. For reference. Exemplarily, in this embodiment, the beating degree is controlled as follows: At this point, the fiber water retention value is approximately 1.6 g / g, and the wet weight weighted average fiber length is approximately 1.0 mm.

[0044] The relationship between freeness and specific pulping energy consumption can be expressed as:

[0045]

[0046] in, For initial beating, the typical value for a mixed softwood and broadleaf pulp is 15 to... ; The energy consumption for pulping is expressed in kWh / t. This is the proportionality coefficient, in units of... When the mixed softwood and broadwood pulp is mixed in a 4:6 ratio, the concentration is usually in the range of 0.08 to 0.12, and in this example, it is 0.10. This is an exponent, typically ranging from 0.6 to 0.8. For example, when... , , At that time, the beating degree was changed from Upgraded to The required specific energy consumption for pulping is approximately 100 to 130 kWh / t.

[0047] The water retention value of fibers after beating is linearly positively correlated with the degree of beating.

[0048]

[0049] in, The slope coefficient is 0.025 to 0.035 g / (g·°SR) for mixed softwood and broadwood pulp, and 0.030 in this example; The intercept is approximately 0.3 to 0.5 g / g; in this example, it is 0.40. When hour, The value was within a reasonable range of 1.2 to 1.8 g / g, which reflects that the fiber achieved moderate internal fiberization and swelling under semi-free and semi-viscous pulping conditions.

[0050] The tensile index of blended pulp paper sheets can be estimated according to the blending rules:

[0051]

[0052] in, For the mass ratio of softwood pulp; The tensile index of the softwood pulp is typically 80 to 100 N·m / g, and in this example it is 90 N·m / g. The tensile index is for broadleaf pulp, typically ranging from 40 to 60 N·m / g; in this example, it is 50 N·m / g. hour, The subsequent quantitative approach The tensile strength of the base paper is approximately It meets the engineering performance target of a longitudinal tensile strength of not less than 3.0 kN / m for food packaging paper.

[0053] In an alternative embodiment, the pulping equipment can also use a conical mill instead of a disc mill. The conical mill provides more precise control over the cutting of long fibers and is suitable for scenarios where there are higher requirements for the uniformity of fiber length distribution.

[0054] S100, the pulp fibers are subjected to intra-pulp crosslinking treatment to form a hydrophobic crosslinking network containing residual active groups on the surface of the pulp fibers, thereby obtaining modified pulp.

[0055] like Figure 2 As shown, the intra-slurry crosslinking treatment uses the pulp suspension produced by S000 as the starting material, and achieves chemical modification of the fiber surface by sequentially adding cationic modified starch and a wet strength agent. The cationic modified starch adsorbs on the fiber surface to provide polyhydroxy reaction sites, and the wet strength agent contains nitrogen heterocyclic active groups. The nitrogen heterocyclic active groups react with the polyhydroxy reaction sites and cellulose hydroxyl groups to form the hydrophobic crosslinking network.

[0056] S110 involves adding gelatinized cationic modified starch to the slurry, allowing it to be coated onto the fiber surface via electrostatic adsorption.

[0057] Weigh cationic modified starch, wherein the degree of substitution of the cationic modified starch is 0.03 to 0.05 and the degree of cationicity is 2.0 to 3.5 meq / g. Add the cationic modified starch to deionized water at a solid content of 10 wt%, and heat at 90°C to... Heat and stir in a water bath for 30 minutes until completely gelatinized and transparent, then cool to... spare.

[0058] The gelatinized starch solution was added to the pulping slurry at a rate of 2.0% (relative to the oven-dry weight of the slurry). The temperature of the slurry was maintained at 40°C. The stirring speed was 300 to 500 rpm, and the stirring time was 10 min. The cationic modified starch molecules uniformly adsorbed and coated the fiber surface in the form of a monolayer through electrostatic attraction between the positive charge they carry and the negative charge (carboxyl and sulfonic acid groups) on the surface of cellulose fibers, providing a high density of hydroxyl reaction sites for subsequent crosslinking agents.

[0059] The adsorption behavior of the cationic modified starch on the fiber surface conforms to the Langmuir monolayer adsorption model:

[0060]

[0061] in, This represents the actual adsorption capacity, expressed in mg / g fiber. For maximum adsorption, the typical value of cationic starch on the surface of bleached wood pulp fibers is 15 to 25 mg / g, and 20 mg / g is used in this example; The Langmuir adsorption constant reflects the adsorption affinity, with typical values ​​ranging from 0.5 to 2.0 L / mg; in this example, it is taken as 1.0 L / mg. For equilibrium concentration, the unit is mg / L.

[0062] For example, the calculation is performed using the processing of 1 ton of oven-dry pulp. The total pulp volume is 25,000 L (4% concentration), the starch addition is 20 kg (oven-dry), and the initial addition concentration is 800 mg / L. Since the total fiber mass is... Furthermore, the maximum adsorption capacity is 20 mg / g, and the adsorption capacity of fiber for starch is much greater than the amount added, resulting in an actual equilibrium concentration. Extremely low, with a starch retention rate of approximately 70% to 85%. Assuming a 75% retention rate, each gram of fiber actually adsorbs about 15 mg of starch, resulting in a fiber surface coverage rate of... .

[0063] The starch adsorption process simultaneously alters the zeta potential of the slurry system. The zeta potential of untreated fibers is approximately -25 mV. After adding cationic starch, the negative charge on the fiber surface is partially neutralized, raising the zeta potential to -15 to -12 mV. Controlling the zeta potential within the range of -10 to -5 mV can prevent excessive flocculation at the isoelectric point.

[0064] In another embodiment, the cationic modified starch can also be replaced by cationic guar gum or cationic carboxymethyl cellulose. Their working principle is the same, both adsorbing onto the fiber surface through cationic charge and providing multiple hydroxyl reaction sites. The difference lies in the different hydroxyl density and molecular weight distribution, which are suitable for scenarios with special requirements for the flexibility or viscosity of the adsorption layer.

[0065] S120 involves adding a wet strength agent to the slurry and controlling the reaction conditions to crosslink the nitrogen heterocyclic active groups of the wet strength agent with the hydroxyl groups on the fiber surface to form a hydrophobic network.

[0066] After 10 min of cationic modified starch adsorption, polyamide polyamine epichlorohydrin resin wet strength agent is added to the slurry. The polyamide polyamine epichlorohydrin resin is an aqueous solution with a solid content of 12.5%, added at a rate of 0.5% (relative to the oven-dry weight of the slurry). For example, 40 kg of polyamide polyamine epichlorohydrin resin solution (containing 5 kg of active ingredient oven-dry) is required to treat 1 ton of oven-dry slurry.

[0067] After adding polyamide polyamine epichlorohydrin resin, adjust the pH of the slurry to 7.5 to 8.0 with a dilute sodium hydroxide solution, and then heat to [temperature missing]. Continue stirring for 20 minutes. The reaction conditions for the intra-slurry crosslinking treatment are: slurry pH value of 7.0 to 8.5, reaction temperature of 40°C to... The stirring time is no less than 15 min. Under alkaline conditions, the aziridine groups (i.e., the three-membered nitrogen heterocyclic active groups, aziridine rings) on the polyamide polyamine epichlorohydrin resin molecular chain undergo a nucleophilic ring-opening reaction. The hydroxyl groups of cellulose on the fiber surface and the hydroxyl groups of the cationic modified starch molecules adsorbed thereon act as nucleophiles to attack the carbon atoms on the aziridine ring, forming carbon-oxygen covalent bonds, bridging the polyamide polyamine epichlorohydrin resin molecules between the cellulose fibers and the modified starch, and constructing a three-dimensional cross-linked network structure.

[0068] The crosslinking reaction follows a second-order reaction kinetic model:

[0069]

[0070] in, This represents the concentration of aziridine ring, in mol / L. The concentration of usable hydroxyl groups is expressed in mol / L, with typical values ​​ranging from 0.1 to 0.5 mol / L. This is a second-order rate constant, expressed in L / (mol·min). The rate constant changes with temperature according to the Arrhenius relation. , of which activation energy It is approximately 50 to 70 kJ / mol.

[0071] The target for controlling the reaction conditions is to achieve a crosslinking conversion rate. The crosslinking conversion rate is defined as 0.4 to 0.6.

[0072]

[0073] in, This represents the initial concentration of the aziridine ring. for Concentration of aziridine ring at time. At pH 7.5 and temperature... Under a reaction time of 20 min, approximately 40 to 60% of the aziridine rings and hydroxyl groups complete the cross-linking reaction, forming a hydrophobic cross-linked network. The technical significance of controlling the cross-linking conversion rate within the range of 0.4 to 0.6 lies in the fact that the reacted aziridine rings contribute to the structural integrity of the hydrophobic cross-linked network on the fiber surface, while the unreacted 40 to 60% residual aziridine groups remain on the fiber surface, becoming active sites for the subsequent chemical anchoring of amino-containing natural polysaccharide molecules in the S400 surface coating stage. The retention of these residual active groups is achieved through mild reaction conditions, and complete thermosetting is delayed until the S500 drying stage at 80°C. Completed under high temperature conditions.

[0074] After intramolecular crosslinking modification, the chemical properties of the fiber surface change as follows: Before modification, the cellulose fiber surface is rich in hydroxyl groups, and the water contact angle is approximately 25° to... It exhibits strong hydrophilicity. After modification, the fiber surface is covered by the crosslinking product of modified starch and polyamide polyamine epichlorohydrin resin, resulting in reduced surface polarity. The contact angle of the modified fiber surface can be estimated using a surface coverage weighted model.

[0075]

[0076] in, The contact angle of the modified fiber surface; The starch coverage is approximately 0.6 under the conditions of 2.0% starch addition and 75% retention. The contact angle of the cross-linked product-covered region is approximately 85° to 100°. ; The contact angle of the naked cellulose surface is approximately 25° to 10°. In this embodiment, For example, ,get After modification, the fiber surface changes from hydrophilic to weakly hydrophobic, with the contact angle typically ranging from 65° to... Within the range.

[0077] After adding polyamide polyamine epichlorohydrin resin, the zeta potential of the slurry further increased from -15 to -12 mV to -10 to -5 mV. The reaction endpoint was defined as the slurry's zeta potential stabilizing in the -10 to -5 mV range after the reaction was completed. The modified slurry after the reaction can be... The following is temporarily saved, awaiting the subsequent papermaking process.

[0078] The in-slurry crosslinking modification not only achieves the direct functions of hydrophobication of the fiber surface and construction of the crosslinking network, but also produces an indirect function that is crucial to the subsequent surface coating stage: the change in the chemical polarity of the modified fiber surface improves the wetting and spreading properties of the polysaccharide coating solution with pH 4 to 5 on the paper substrate surface, resulting in a more uniform and dense coating film.

[0079] Another technical effect of the intra-pulp crosslinking modification is to enhance the inter-fiber bonding force. Polyamide polyamine epichlorohydrin resin molecules act as crosslinking bridges, with multiple aziridine active groups on their molecular chains reacting with hydroxyl groups on the surfaces of adjacent fibers to form inter-fiber covalent crosslinks in the fiber junction region. These inter-fiber covalent crosslinks are not destroyed by water molecules under wet conditions (unlike the dry strength mechanism of cellulose fibers which relies on hydrogen bonding), thus imparting wet strength to the paper-based material. The contribution of enhanced inter-fiber bonding force to the paper-based strength can be understood through the Page equation:

[0080]

[0081] in, Tensile strength index; This represents the zero-span tensile strength of the fiber. The cross-sectional area of ​​the fiber; Paper density; Shear strength of the interfiber bonding force; The fiber circumference; Fiber length; This refers to the relative bonding area. The intra-slurry crosslinking modification improves... (interfiber bond shear strength) and (Modified starch increases the effective bonding area) Two parameters are used to enhance the tensile strength of the paper sheet. Under the conditions of this embodiment, the dry strength gain of 0.5% polyamide polyamine epichlorohydrin resin is approximately 5% to 15%, corresponding to an increase in the tensile index of the paper sheet from 66 N·m / g to approximately 70 to 76 N·m / g. Under wet conditions, the wet strength of unmodified paper sheet is typically only 3% to 5% of its dry strength, while the wet strength after crosslinking modification with polyamide polyamine epichlorohydrin resin can reach 15% to 25% of its dry strength. Maintaining this wet strength is of great technological significance for preventing the paper sheet from breaking during the subsequent coating process when it is wet and undergoes sizing and pressing.

[0082] In another embodiment, the wet strength agent can also be a polycarbodiimide crosslinking agent instead of polyamide polyamine epichlorohydrin resin. The carbodiimide groups in the polycarbodiimide molecule can react with carboxyl groups to form acylurea bonds, which can also build a crosslinking network on the fiber surface. The residual carbodiimide groups after the reaction can serve as active sites for subsequent chemical anchoring. The difference lies in the different types of chemical bonds formed, which is suitable for application scenarios with higher requirements for the pH tolerance of paper-based materials.

[0083] S200, the modified slurry is formed into a paper base.

[0084] The papermaking process uses the modified pulp produced by S100 as the starting material, and after dilution, web forming, pressing and dewatering and pre-drying, a base paper substrate containing a hydrophobic cross-linked network structure is obtained.

[0085] The modified pulp produced by S100 was diluted from a concentration of 4 wt% to a papermaking concentration of 0.5 wt%. During the dilution process, a microparticle retention aid system was added. This system consisted of cationic polyacrylamide and bentonite, with the cationic polyacrylamide added at 0.02 to 0.05% (octane-dry pulp weight) and the bentonite added at 0.1 to 0.3% (octane-dry pulp weight). This microparticle retention aid system improved the first-pass retention rate of fine fibers and cationic modified starch in the modified pulp to over 85% through a bridging flocculation mechanism, ensuring the integrity of the intraparticle cross-linked network structure in papermaking. The diluted pulp was then purified by a sand separator and a pressure screen.

[0086] The pulp is evenly distributed onto the wire surface of the wire forming machine via a hydraulic full-width headbox, with the pulp velocity ratio controlled within the range of 0.95 to 1.05 to balance the longitudinal and transverse strength of the paper web. Because the modified pulp contains cationic modified starch and polyamide polyamine epichlorohydrin resin, the system has an increased tendency to flocculate; therefore, the turbulence intensity in the headbox needs to be maintained at a Reynolds number greater than 40,000 to ensure uniform fiber dispersion on the wire surface.

[0087] The uniformity of fiber dispersion on the forming mesh can be assessed by the relationship between floc size and slurry concentration. The empirical relationship between the average diameter of fiber flocs and slurry volume concentration and fiber length is as follows:

[0088]

[0089] in, This represents the average diameter of the fiber flocs, in mm. This is the volume concentration of the slurry (dimensionless decimal). A mass concentration of 0.5 wt% corresponds to a volume concentration of approximately 0.00033. The weighted average fiber length is in mm. The pulping time for a 4:6 mixture of softwood and broadleaf fibers is... The diameter is approximately 1.0 mm. Empirical constants (dimensionless, when...) related to fiber stiffness and surface friction dimensionless decimals, When using mm Output unit is mm), bleached chemical pulp The value is typically taken in the range of 400 to 550; in this embodiment, 440 is used. For example, Based on this clump size, the paper basis weight... The coefficient of variation of the time base weight is approximately 0.72%, which is lower than the excellent uniformity standard of 1%, meeting the requirements of coated base paper for surface uniformity.

[0090] The wet paper web passes sequentially through a forming wire, a wet suction box, and a vacuum suction box for dewatering, with the paper web exiting the wire section having a dryness of approximately 18% to 22%. The wet paper web then enters the press section, where it undergoes three-roll press dewatering. The press dewatering process follows the Wahlstrom press model:

[0091]

[0092] in, To achieve the desired degree of dryness; To determine the degree of dryness upon pressing; To achieve the maximum achievable dryness increase, chemical pulp requires approximately 25% to 30%; The pressing pulse is equal to the product of linear pressure and residence time; To characterize the press pulse constant, bleached chemical pulp typically ranges from 100 to 200 kPa·s. The pressures of the three press lines are 60 to 80 kN / m, 80 to 100 kN / m, and 100 to 120 kN / m, respectively, increasing the paper web dryness at the press exit to 40 to 45%.

[0093] The pressure on the press line also determines the paper density. The target density is 0.6 to... , for example, quantitative The paper sheet has a thickness of approximately 71 μm after three presses, and a density of [missing information]. If the paper density is too high, the air permeability will be too low, which is not conducive to the proper penetration of the coating liquid into the fiber gaps; if the density is too low, the paper surface roughness will be high, which is not conducive to coating uniformity.

[0094] After pressing, the paper web enters the pre-drying section, where moisture is evaporated by multiple drying cylinders. The surface temperature of the drying cylinders is maintained at 80°C to... Incremental distribution. The incremental temperature design of the pre-drying section has a significant impact on the cross-linking network within the slurry: the initial low-temperature section mainly evaporates free water, while the temperature rises to 100°C in the later stage. This process begins to promote further cross-linking and curing of the polyamide polyamine epichlorohydrin resin, gradually increasing the strength of the cross-linked network structure on the fiber surface. After the pre-drying section, the moisture content of the paper web drops to 5-8%, and it is then wound into a master roll for later use.

[0095] The contribution of the pre-drying section to the crosslinking conversion rate needs to be precisely controlled. During the S100 slurry in-slurry crosslinking stage ( (20 min), the crosslinking conversion rate reaches approximately 0.4 to 0.6. Although the temperature in the later stage of the pre-drying section rises to 100 to... However, the paper web only remains in this temperature range for a few seconds to a dozen seconds (depending on the machine speed and the number of high-temperature cylinders), far shorter than the time required for complete curing. Using the Arrhenius relation, The curing rate constant at the following conditions is approximately The crosslinking conversion rate increases by 3 to 5 times under a residence time of 10 s, with an increase of approximately 0.03 to 0.08. Therefore, the total crosslinking conversion rate after the pre-drying stage is approximately 0.45 to 0.65, and approximately 35% to 55% of unreacted residual aziridine groups remain on the fiber surface. The retention of these residual groups is crucial for subsequent S400 chemical anchoring: if the pre-drying temperature is too high or the residence time is too long, causing the crosslinking conversion rate to reach above 0.9 prematurely, most of the residual active groups will be consumed, preventing the chitosan amino groups from forming an effective chemical anchor with the paper base in the S400 stage. For example, at a speed of 100 m / min, the high-temperature zone of the pre-drying stage ( The number of drying cylinders should be controlled within 2 to 3, corresponding to a high-temperature residence time of about 6 to 9 seconds, to ensure that the residual groups are fully preserved.

[0096] The basis weight of the base paper is 40 to The target quantification in this embodiment is The white water recycling system reuses dehydrated white water from the mesh section. It is necessary to regularly monitor the accumulation of cationic modified starch and the zeta potential of the white water to maintain the stability of the system's charge balance.

[0097] In an alternative embodiment, the paper forming process can also use a wire mesh forming device instead of a long wire mesh forming device. Wire mesh forming enables simultaneous dehydration on both sides of the paper web, resulting in better uniformity and smaller difference between the two sides. It is suitable for low basis weight lightweight base paper with higher requirements for coating uniformity.

[0098] S300 is an oil-resistant coating liquid formulated with amino-containing natural polysaccharides as the main component.

[0099] like Figure 3 As shown, the oil-repellent coating liquid is formulated using chitosan, cellulose nanofibers, and sodium alginate as raw materials. Through stepwise dissolution, mixing, and ionic cross-linking pre-assembly, a ternary polysaccharide oil-repellent sizing liquid with suitable rheological properties is obtained. The oil-repellent coating liquid also contains nanocellulose and carboxyl-containing natural polysaccharides. The amino-containing natural polysaccharides and the carboxyl-containing natural polysaccharides form an ionic cross-linked pre-assembled structure through electrostatic interactions between the amino and carboxyl groups.

[0100] S310 was used to dissolve each polysaccharide component separately to obtain chitosan solution, cellulose nanofiber suspension and sodium alginate solution.

[0101] Weigh out chitosan powder, wherein the degree of deacetylation of the chitosan is not less than 85% and the molecular weight is 300,000 to 500,000. Add the chitosan to a 1 wt% aqueous acetic acid solution and heat at 40°C to... The chitosan solution was prepared by magnetic stirring in a water bath for 2 to 4 hours until completely dissolved and transparent, resulting in a 2.0 wt% chitosan solution. Chitosan molecules dissolve under acidic conditions by protonation of the amino groups into ammonium ions. The degree of protonation of the chitosan amino groups and the pH of the solution follow the Henderson-Hasselbalch equation.

[0102]

[0103] in, The degree of amino protonation of chitosan. Approximately 6.3. When the pH of the coating solution is 4.5, That is, about 98% of the amino groups are in a protonated state, and the chitosan is completely dissolved.

[0104] Sodium alginate powder was weighed and added to deionized water to prepare a 2.0 wt% solution. The solution was stirred at room temperature for 1 to 2 hours until completely dissolved. Sodium alginate is an anionic polysaccharide, and its carboxyl groups exist in a dissociated state at pH greater than 3.5. A cellulose nanofiber suspension (solid content 2.5 wt%) was treated with a high-shear disperser at 10,000 to 15,000 rpm for 5 minutes to fully disentangle and disperse the nanofibers into a stable suspension. The cellulose nanofibers had a diameter of 5 to 30 nm, a length of 1 to 5 μm, and an aspect ratio typically in the range of 100 to 500.

[0105] S320 involves mixing the various polysaccharide components according to the specified ratio and triggering ionic cross-linking pre-assembly to form a coating solution with suitable rheological properties.

[0106] Chitosan, cellulose nanofibers, and sodium alginate were mixed at a solid content mass ratio of 5:3:2. The order of addition was as follows: first, the cellulose nanofiber suspension was added to the chitosan solution and stirred for 5 minutes to ensure uniform dispersion of the cellulose nanofibers in the chitosan matrix; then, the sodium alginate solution was slowly added while continuously stirring. The addition of the sodium alginate solution triggered the electrostatic interaction between the ammonium ions of chitosan and the carboxyl anions of sodium alginate, forming a pre-assembled polyelectrolyte complex structure.

[0107] like Figure 13 As shown, the degree of ionic cross-linking is determined by the charge ratio. control:

[0108]

[0109] in, For chitosan quality; The degree of deacetylation is not less than 0.85; The degree of amino protonation of chitosan; The molecular weight of the glucosamine unit is 161 g / mol; For sodium alginate quality; The degree of dissociation of the carboxyl group of sodium alginate is approximately 0.91 at pH 4.5; The average molecular weight of the uronic acid unit is 198 g / mol. For example, taking the preparation of 10 kg of coating solution as an example, the total solid content is 2.0 wt%, i.e., 200 g of total solids. This includes 100 g of chitosan, 60 g of cellulose nanofibers, and 40 g of sodium alginate. The molar number of positive charges of chitosan is... Moles of negative charge of sodium alginate , The charge ratio is within the operating window of 1.5 to 3.0, with a moderate excess of positive charge in chitosan, ensuring that the mixture remains fluid while forming ionic cross-linked preassemblies and does not gel into an uncoatable solid.

[0110] After mixing, deionized water was added to adjust the total solids content to 2.0 wt%, and the pH was finely adjusted to 4.5 with 1 wt% acetic acid or 1 wt% sodium hydroxide. The mixture was degassed under vacuum for 15 to 30 minutes to remove air bubbles introduced during stirring.

[0111] The coating solution must be stored and used under specified conditions after preparation. Because the ionic crosslinking between chitosan and sodium alginate is a dynamic and reversible process, the coating solution can maintain a stable flow state at pH 4.5 and room temperature. However, after prolonged storage, the ionic crosslinking network will slowly grow, leading to a gradual increase in viscosity. The coating solution is usable within 24 hours of preparation. Under the specified storage conditions, if this time is exceeded, the viscosity should be retested, and if necessary, the pH should be lowered to 4.0 by adding dilute acetic acid to partially dissociate the ionic crosslinks and restore fluidity. The storage temperature should not exceed [specific temperature range]. Excessively high temperatures will accelerate the movement of chitosan chain segments and increase the density of ionic crosslinking. Storage temperatures should also not be lower than [specific temperatures should be specified]. At excessively low temperatures, the suspension stability of cellulose nanofibers decreases, potentially leading to localized flocculation and sedimentation. The coating solution must be filtered through a 200-mesh screen before use to remove any microgel particles that may be generated, ensuring a smooth coating surface.

[0112] like Figure 12 As shown, the rheological behavior of the coating liquid exhibits pseudoplastic characteristics, and the relationship between apparent viscosity and shear rate follows a power-law fluid model:

[0113]

[0114] in, Apparent viscosity, in Pa·s; This is the consistency coefficient, in units of... ; Shear rate, in units of ; The flow behavior index for cellulose nanofiber suspensions is typically in the range of 0.3 to 0.6. This pseudoplasticity means that the viscosity of the coating solution decreases in the high-shear zone of the sizing press roll gap, which is beneficial for film transfer, while the viscosity recovers in the low-shear zone after the roll, which is beneficial for coating settling. In this embodiment, the coating solution exhibits a shear rate... ,temperature The apparent viscosity under the given conditions is 200 mPa·s, which falls within the suitable coating range of 50 to 500 mPa·s.

[0115] The barrier enhancement effect of cellulose nanofibers in coated dry films can be described by a tortuosity factor model:

[0116]

[0117] in, The tortuosity factor characterizes the extension factor of the oil penetration path relative to the film thickness direction; The aspect ratio of cellulose nanofibers is typically in the range of 100 to 500; in this example, it is taken as 200. This represents the volume fraction of cellulose nanofibers in the dry film. For example, the cellulose nanofibers comprise 30 wt% of the dry film's solid content, after density correction (the density of cellulose nanofibers is approximately...). The density of the chitosan matrix is ​​approximately ), , The tortuosity factor indicates that the actual penetration path of oil molecules in the coating is extended by approximately 29 times, which enhances the oil-repellent barrier effect. During the subsequent S500 gradient drying stage, the cellulose nanofibers undergo in-plane orientation under stress-induced stress, further increasing the tortuosity factor to 49.

[0118] In another embodiment, the amino-containing natural polysaccharide can also be replaced by chitosan oligosaccharide. The lower molecular weight of chitosan oligosaccharide reduces the viscosity of the coating liquid, making it suitable for the low viscosity requirement under high-speed coating conditions. At the same time, chitosan oligosaccharide molecules still contain a large number of free amino groups that can participate in chemical anchoring reactions.

[0119] In an alternative embodiment, sodium carboxymethyl cellulose can be used instead of sodium alginate as a natural polysaccharide component with carboxyl groups. Sodium carboxymethyl cellulose can also form a polyelectrolyte complex with chitosan. The difference is that the molecular chain of sodium carboxymethyl cellulose is more flexible, and the resulting coating has better flexibility, making it suitable for packaging applications that require higher folding resistance.

[0120] S400, the oil-resistant coating liquid is applied to the surface of the paper base, and the amino groups of the polysaccharide molecules in the oil-resistant coating liquid react with the residual active groups of the cross-linked network on the surface of the paper base fiber to form a chemical anchor, thereby obtaining a polysaccharide oil-resistant lightweight packaging paper base material.

[0121] like Figure 4 As shown, the surface coating uses the base paper substrate produced by S200 and the ternary polysaccharide oil-resistant sizing liquid produced by S300 as input materials. The coating liquid is transferred to the paper substrate surface by sizing and pressing, and chemical anchoring bonding between the polysaccharide coating and the paper substrate is achieved during the coating process.

[0122] S410 transfers the coating liquid to the paper base surface via sizing press, controlling the coating amount within the target range.

[0123] The ternary polysaccharide oil-resistant sizing solution produced by S300 is transferred from the constant-temperature storage tank to the sizing and pressing tray, with the liquid temperature controlled at 40°C. To moderately reduce viscosity and promote subsequent chemical anchoring reactions, the base paper produced by S200 is unwound and introduced into the coating section, with the paper web tension controlled between 0.5 and 1.0 kN / m. As the paper web passes through the sizing press rolls, both sides simultaneously come into contact with the coating liquid, and under the pressure of the rolls, the liquid film is transferred to the surface of the paper web to form a uniform thin coating.

[0124] The coating amount is controlled by the pressure and speed of the sizing press line. The empirical relationship between the coating amount and process parameters is as follows:

[0125]

[0126] in, This refers to the amount of coating applied dry, in units of... ; The pressure of the sizing press line is measured in kN / m and is typically adjusted within the range of 20 to 60 kN / m. The unit is vehicle speed, expressed in m / min. Increasing the linear pressure or vehicle speed reduces the coating weight. In this embodiment, the linear pressure is set to 35 to 40 kN / m and the vehicle speed to 100 m / min. Under these conditions, the oven-dry coating weight is approximately... (Total of both sides).

[0127] For example, with a coating liquid solid content of 2.0 wt%, the oven-dry coating weight is calculated as follows: The corresponding wet coating amount is (Total for both sides), the wet coating amount per side is approximately The thickness of the single-sided dry coating after drying is... (Coating density is taken as) The total thickness of the double-sided dry coating is approximately 1.8 μm. After coating, the paper basis weight increases from... Increase to The quantitative increase was only 5%, which meets the design goal of lightweight packaging paper.

[0128] The difference in paper web basis weight before and after coating is detected online in real time by a β-ray basis weight sensor, and the pressure of the sizing press line is adjusted accordingly to control the coating amount fluctuation within 10% of the set value.

[0129] S420, the coating liquid wets and spreads on the modified paper base surface, and the chitosan amino reacts with the residual active groups on the paper base surface to form a chemical anchor.

[0130] The wetting and spreading behavior of the coating liquid upon contact with the paper substrate surface is controlled by the chemical properties of the paper substrate surface. The contact angle of the paper substrate surface modified by S100 internal crosslinking is approximately The spreading behavior of the coating liquid on this weakly hydrophobic surface satisfies the ideal condition of "spreading but not excessive penetration". The capillary penetration of the coating liquid on the paper substrate surface follows the Washburn equation:

[0131]

[0132] in, The depth of penetration; The equivalent radius of the interfiber capillary; The surface tension of the coating liquid is approximately ; The contact angle of the coating liquid on the paper substrate surface; The viscosity of the coating solution; The penetration time. When the contact angle of the paper substrate surface is in an unmodified state. Upgraded to modified hour, This means that the capillary penetration rate of the modified coating solution decreased to 39.5% of that of the unmodified paper base. Within the same coating contact time, the penetration depth of the coating solution on the modified paper base was approximately [amount missing] of that on the unmodified paper base. This results in more coating liquid remaining on the paper substrate surface to form a continuous liquid film. The synergistic effect of the pulp modification on the coating process is manifested in the fact that the cross-linking network within the pulp reduces the hydrophilicity of the fiber surface, causing the coating liquid to no longer rapidly penetrate into the fiber network through capillary action, but instead spread and form a film on the paper substrate surface, thereby achieving continuous coating coverage even with low coating amounts.

[0133] The surface coverage integrity of the coating can be quantitatively assessed by the effective surface retention rate. The surface retention rate is defined as the proportion of coating liquid actually remaining on the paper substrate surface relative to the total applied amount. Based on the difference in penetration rate caused by the change in contact angle before and after modification in the Washburn equation (the penetration rate after modification decreases to 39.5% of the unmodified state), and combined with the operating condition of approximately 1 s contact time between the sizing and press rolls, the following estimation is made: For unmodified paper substrates, approximately 50% to 70% of the coating liquid enters the fiber network during the sizing and press contact time due to capillary penetration loss, resulting in a surface retention rate of only 30% to 50%; for modified paper substrates, the reduced penetration rate increases the surface retention rate to 60% to 80%. The absolute dry coating amount is used as the basis for this estimation. It is estimated that the actual amount of residue retained on the modified paper base is approximately 1.5 to... With coating density The calculated dry coating thickness is approximately 1.1 to 1.4 μm, which is sufficient to cover the microscopic roughness of the paper substrate surface. On unmodified paper substrates, the surface residue for the same coating amount is only 0.75 μm. The corresponding dry coating thickness is approximately 0.5 to 0.9 μm, which is insufficient to completely cover microscopic defects on the paper surface, significantly increasing the probability of discontinuous pinholes in the coating. The comparison shows that in-slurry crosslinking modification ensures coating continuity under low coating weight conditions by improving surface retention, which is a key technological basis for achieving lightweighting through dual-layer synergy.

[0134] Upon contact with the paper substrate surface, the free amino groups of the chitosan molecular chains in the coating solution undergo nucleophilic addition reactions with the residual aziridine groups retained in the hydrophobic crosslinking network, forming carbon-nitrogen covalent bonds. The rate equation for the chemical anchoring reaction is:

[0135]

[0136] in, The areal density of residual aziridine rings on the paper substrate surface, in units of ; This refers to the amino concentration of chitosan in the contact area of ​​the paper substrate surface; This represents the anchoring reaction rate constant. Because amino groups are more nucleophilic than hydroxyl groups, the anchoring reaction rate constant is approximately 3 to 5 times that of the hydroxyl crosslinking reaction in the S100 stage. At a coating temperature of 40°C to... Under these conditions, the roller contact time is approximately 1 second, and the residence time from the roller end to the dry section inlet is approximately tens of seconds. This time window is sufficient for the chitosan amino groups to form preliminary chemical bonds with the residual aziridine groups. Complete anchoring and curing occur at 80% of the S500 stage. Completed under high temperature conditions.

[0137] The chemical anchoring density can be estimated using the following method: Based on a 0.5% addition of polyamide polyamine epichlorohydrin resin (relative to oven-dry pulp weight), each gram of fiber carries 5 mg of active ingredient. The specific surface area of ​​bleached chemical pulp fibers is approximately 3 to... / g, in this embodiment, we take / g. The molecular weight of polyamide polyamine epichlorohydrin resin is approximately 500,000, with each molecular chain containing approximately 200 aziridine rings. The crosslinking conversion rate in the S100 stage is 0.4 to 0.6, with a residual proportion of approximately 40% to 60%, meaning that each molecular chain retains approximately 80 to 120 unreacted aziridine rings. (Based on fiber specific surface area...) Based on / g, the residual aziridine toroidal density is on the order of approximately to For example, the residual surface density is taken as... After coating, the amount of amino groups supplied to chitosan at the interface is much greater than the amount of residual groups (the amino density of chitosan is approximately...). Therefore, the anchoring reaction is concentration-limited by the residual aziridine groups. Under the combined action of the S400 coating stage and the S500 thermosetting stage, the anchoring conversion rate of the residual aziridine groups can reach 60% to 80%, with a final effective anchoring density of approximately... to The interfacial covalent bond spacing corresponding to this anchoring density is on the order of 20 to 30 nm, which is sufficient to firmly anchor the chitosan coating network to the paper-based fiber surface at the molecular scale.

[0138] The chemical anchoring enhances the bonding force between the coating and the paper substrate from physical adsorption to covalent bonding. Under wet or grease-impregnated conditions, physically adsorbed coatings are prone to peeling and failure due to hydrogen bond breakage, while covalently anchored coatings maintain the integrity of the interfacial structure under the same conditions.

[0139] like Figure 6 As shown, the microscopic mechanism of the chemical anchoring reaction is as follows: unreacted aziridine groups remain on the polyamide polyamine epichlorohydrin resin molecular chain on the paper-based fiber surface. The amino nitrogen atom of chitosan launches a nucleophilic attack on the three-membered ring carbon atom of the aziridine group, and the aziridine ring opens to form a carbon-nitrogen covalent bond, which covalently connects the chitosan molecular chain to the cross-linking network on the surface of the paper-based fiber.

[0140] In another embodiment, the coating liquid can also be applied by a doctor blade coating method instead of sizing and pressing. Doctor blade coating has higher measurement accuracy for coating amount and is suitable for application scenarios with stricter requirements for coating thickness uniformity. The difference is that the doctor blade applies a larger shear force to the paper base, which requires the paper base to have higher wet strength.

[0141] In an alternative embodiment, the chemical anchoring can also be achieved through an amide bond formation mechanism. That is, when the wet strength agent is a crosslinking agent containing isocyanate residual groups, the amino groups of chitosan in the coating liquid react with the isocyanate groups to form urea bonds, thus achieving covalent bonding between the coating and the paper base. This is suitable for packaging scenarios with higher requirements for alkali resistance.

[0142] S500 involves gradient heating and drying curing of the coated paper base to thermally cure the hydrophobic crosslinking network and densify the polysaccharide coating on the paper base surface to form a continuous, non-porous barrier film.

[0143] like Figure 7 As shown, the drying and curing process uses the wet coated paper produced by S400 as the input material, and completes the triple functions of moisture evaporation, polysaccharide coating densification, and cross-linked network thermal curing simultaneously through a gradient heating drying cylinder.

[0144] The wet-coated paper first passes through an infrared pre-drying section, where infrared radiation rapidly evaporates free water on the coating surface, allowing the coating to initially set and preventing it from being transferred and stuck to the drying cylinder surface when it comes into contact with the drying cylinder. After pre-drying, the moisture content of the coating decreases from approximately 90% to 60-70%.

[0145] S510, through the first drying zone, gently evaporates the free water from the coating.

[0146] like Figure 9 As shown, the paper web passes through 4 to 6 drying cylinders, with cylinder surface temperatures ranging from 80 to... This stage is a constant-rate drying period, during which free water in the coating evaporates at a constant rate. The coating volume shrinks, but the polysaccharide molecular chains still have sufficient fluidity for conformational rearrangement. Gentle drying avoids rapid skin formation on the coating surface, which can block internal moisture channels.

[0147] S520 promotes the formation of hydrogen bonds between polysaccharide molecular chains through medium-temperature drying in the second drying zone.

[0148] The paper web passes through 6 to 8 drying cylinders, with cylinder surface temperatures ranging from 100 to... During this stage, the drying rate decreases, and moisture migration is controlled by diffusion within the coating. The interchain spacing of polysaccharides in the coating shrinks to the range of hydrogen bonding, and a large number of intermolecular hydrogen bonds begin to form. The ionic crosslinking network between chitosan and sodium alginate further tightens, accelerating the densification of the coating.

[0149] The change in moisture content during the falling-rate drying period follows the Fick diffusion model:

[0150]

[0151] in, For time Moisture content of the coating at that time; This refers to the equilibrium water content of the polysaccharide membrane under ambient humidity conditions, typically ranging from 5% to 8%. The critical water content, i.e., the turning point from the constant rate period to the falling rate period, is approximately 30% to 40% for polysaccharide membranes. The effective diffusion coefficient of moisture in the coating is given; a typical value for polysaccharide membranes is [value missing]. to / s; The half-thickness of the coating is approximately 0.45 μm when the single-sided dry coating is approximately 0.9 μm.

[0152] During the slow-drying period, the in-plane biaxial compressive stress generated by the volume shrinkage of the coating drives the orientation of the dispersed cellulose nanofibers within the coating. The aspect ratio of the cellulose nanofibers is typically in the range of 100 to 500. When the coating shrinks in the thickness direction due to the constraint of the paper-based interface but shrinks freely in the in-plane direction, the high aspect ratio cellulose nanofibers tend to align parallel to each other in the in-plane direction under the shrinkage stress field. The degree of this stress-induced orientation can be measured by the Hermans orientation factor. Characterization:

[0153]

[0154] in, The angle between the long axis of the cellulose nanofibers and the normal direction of the coating plane. This is the statistical average of the square of the cosine of the orientation angle. When the cellulose nanofibers are completely randomly distributed... When fully in-plane orientation (Negative values ​​characterize in-plane preference). Under the gradient drying conditions, the absolute values ​​of the Hermans orientation factor of the cellulose nanofibers in the coating are typically in the range of 0.6 to 0.8, indicating that the cellulose nanofibers have a clear in-plane preferred orientation.

[0155] The in-plane orientation of cellulose nanofibers further extends the penetration path of oil molecules along the coating thickness direction. The tortuosity factor after orientation is improved compared to the random distribution state; the tortuosity factor after orientation correction can be expressed as:

[0156]

[0157] in, The aspect ratio of cellulose nanofibers is taken as 200; The volume fraction of cellulose nanofibers in the dry film is approximately 0.28. This is the absolute value of the Hermans orientation factor. For example, when... hour, The theoretical limit values ​​mentioned above assume that the cellulose nanofibers are rigid, straight rods and perfectly parallel. Under actual engineering conditions, an orientation efficiency correction factor needs to be introduced. To correct the effects of cellulose nanofiber bending, local aggregation, and uneven orientation distribution. Typically within the range of 0.4 to 0.6, the effective tortuosity factor is determined by the ratio of the effective tortuosity factor derived from measured oxygen permeability in literature on cellulose nanofiber composite films to the theoretical limit. In this example, a value of 0.52 is used. The corrected effective tortuosity factor... The tortuosity factor is approximately 69% higher than the random state before drying (29 times the coating thickness). This increase means that the actual penetration path of oil molecules in the coating is extended from 29 times the coating thickness to 49 times, further enhancing the barrier effect of the polysaccharide oil-resistant barrier layer.

[0158] S530 undergoes high-temperature treatment in the third drying zone to achieve thermosetting of the cross-linked network.

[0159] like Figure 10 As shown, the paper web passes through 4 to 6 drying cylinders, with cylinder surface temperatures ranging from 110 to... The main function of this stage is to promote the completion of the thermosetting of the polyamide polyamine epichlorohydrin resin. At 110°C to... Under these conditions, the residual aziridine groups retained in the S100 stage and the chitosan anchored to the polyamide polyamine epichlorohydrin resin formed in the S400 stage are further cross-linked and cured.

[0160] The crosslinking conversion rate of the thermosetting process varies with temperature and time as follows:

[0161]

[0162] in, for Crosslinking conversion rate at any given time; The initial crosslinking conversion rate upon entering the drying section is approximately 0.5 (cumulative contribution from the S100 slurry reaction and the S400 coating stage). The curing rate constant follows the Arrhenius temperature dependence. ,in The activation energy for thermosetting is approximately 40 to 60 kJ / mol. Under the condition, the curing rate constant is approximately 10 to 30 times under the given conditions. For example, when... ,Target At that time, it is necessary to meet the following requirements. Right now .exist Down Approximately 0.5 to The required time is approximately 1.6 to 3.2 minutes. The paper web dwell time in the third drying zone is approximately 1 to 3 minutes, combined with the time in the second drying zone (100 to...). The pre-curing contribution under the given conditions, and the total effective high-temperature curing time meet the target of a crosslinking conversion rate greater than 0.9.

[0163] The coating does not develop cracking defects during the gradient drying process. For example... Figure 11 As shown, the critical crack thickness of the coating can be estimated using the Griffith criterion:

[0164]

[0165] in, The fracture energy of the coating is approximately 1 to 100 kcal / kg. In this embodiment, ; It is Poisson's ratio, approximately 0.35; The coating shear modulus is approximately 0.5 GPa. The linear strain for volumetric shrinkage under gradient drying conditions is approximately 0.04. For example, In this embodiment, the thickness of the single-sided dry coating is approximately 0.9 μm, which is less than the critical crack thickness of 2.0 μm, and the coating will not develop cracks during the drying process.

[0166] One or two cooling cylinders are installed after the third drying zone, with a cylinder surface temperature of 30°C. To prevent heat buildup inside the paper roll after winding, the paper web temperature is lowered to near room temperature. A near-infrared moisture sensor is used to monitor the paper web moisture content online, ensuring the final moisture content is within the range of 5% to 7%. Too low a moisture content increases paper brittleness and reduces folding endurance, while too high a moisture content may cause residual moisture in the coating to affect the film's density. After drying, the paper web is wound up to form the finished master roll.

[0167] After the gradient drying and curing treatment, the polysaccharide oil-resistant barrier layer forms a final dense microstructure. Within the coating, the ionic cross-linking network between chitosan and sodium alginate molecular chains undergoes densification and rearrangement during dehydration and shrinkage, shortening the molecular chain spacing to within the range of hydrogen bonding, forming dense physical cross-linking nodes. Cellulose nanofibers are embedded in the ionic cross-linking network in an in-plane orientation. Their high-rigidity nanofiber skeleton prevents excessive shrinkage and deformation of the coating during drying, while providing mechanical strength support. After thermosetting, the cross-linking conversion rate of the polyamide polyamine epichlorohydrin resin increases from approximately 0.5 initially to over 0.9, and the cross-linking network forms an irreversible covalent three-dimensional network structure. The final coating morphology is a glassy, ​​dense film with an extremely low free volume fraction. Oil molecules cannot penetrate and diffuse through the transient free volume channels formed by the thermal motion of molecular chain segments, thus achieving a continuous, non-porous physical barrier effect. The coating maintains structural stability under both dry and wet conditions and does not swell or crack due to changes in environmental humidity.

[0168] In an alternative embodiment, the gradient drying can also use a hot air convection drying oven instead of a cylinder contact drying. Hot air drying has better temperature uniformity and is suitable for products with higher requirements for coating surface quality. The difference is that the energy efficiency of hot air drying is lower than that of cylinder contact drying.

[0169] S600, the performance of the polysaccharide oil-resistant lightweight packaging paper-based material is tested.

[0170] like Figure 14 As shown, the oil-repellent properties of the finished paper are evaluated using a Kit value test. The Kit value test is performed according to the TAPPIT 559 standard. Twelve different surface tension mixtures of castor oil, toluene, and n-heptane are dropped onto the paper surface. After 15 seconds, the mixture is wiped off, and the paper surface is observed for any signs of wetting or penetration. The Kit value is determined by the lowest surface tension test solution that the paper can block. In this embodiment, the Kit value of the finished paper is not lower than level 8. The surface tension of Kit 8 test solution is approximately 27.3 mN / m, which corresponds to excellent food-grade oil-repellent properties.

[0171] The longitudinal tensile strength of the finished paper was tested according to GB / T 12914 standard. The tensile strength of coated paper can be estimated based on empirical relationships:

[0172]

[0173] in, The tensile index of the base paper is 66 N·m / g (S000 pulp preparation and beating design value). The strength gain ratio resulting from the crosslinking of polyamide polyamine epichlorohydrin resin is typically 0.05 to 0.15, and in this example, it is 0.10. The tensile index of the coating membrane material is approximately 80 to 120 N·m / g for the chitosan and cellulose nanofiber composite membrane, and 100 N·m / g is used in this embodiment. Coating amount ; For paper base basis For example, Quantity based on finished product The longitudinal tensile strength is calculated to be approximately It meets the performance target of not less than 3.0 kN / m.

[0174] The coating adhesion of the finished paper was evaluated using the tape peeling method. After scribbling a cross pattern on the coating surface, 3M 610 tape was applied and quickly peeled off. Under dry conditions, the coating adhesion was no less than 4B (coating peeling area not exceeding 5%), and after immersion in water for 30 minutes, the wet adhesion was no less than 3B. The retention of wet adhesion verified the effectiveness of chemical anchoring. Coatings relying solely on physical adsorption typically only achieve a 0B to 1B rating under wet conditions.

[0175] The air permeability of the finished paper was tested according to GB / T 458 standard, using the Gurley method to determine the time required for 100 mL of air to pass through the sample. The air permeability of the unmodified and uncoated raw paper base was approximately 5 to 15 s / 100 mL. After S100 in-slurry crosslinking modification, the air permeability increased to 20 to 40 s / 100 mL (the crosslinking network blocks some inter-fiber channels). After S400 coating and S500 drying and curing, the air permeability of the finished paper further increased to over 200 s / 100 mL, indicating that the polysaccharide oil-resistant barrier layer formed a continuous and dense film coverage, effectively sealing the micropores on the paper base surface. The progressively increasing air permeability verified the formation process of the double-layer synergistic barrier structure: the bottom crosslinking network first blocks some of the macropores between fibers, and the surface polysaccharide film further covers and seals the remaining micropores, ultimately achieving complete density.

[0176] The water vapor transmission rate of the finished paper was tested according to GB / T 1037 standard, at a temperature The test was conducted under conditions of 90% relative humidity. The water vapor transmission rate of the finished paper in this example is approximately 80% to 150%. 300 to 500 lower than uncoated base paper However, it is significantly higher than that of polyethylene-coated paper by 5 to 10. The fact that the water vapor permeability is within a moderate range indicates that the polysaccharide coating has selective barrier properties: it has a high barrier ability against oil molecules (non-polar macromolecules), but still maintains a certain permeability to water vapor (polar small molecules). This property is beneficial for the moisture regulation of food inside the packaging and avoids the accumulation of condensate that causes the food to become damp.

[0177] The basis weight of the finished paper is (paper base) Add coating The moisture content is 5 to 7%.

[0178] like Figure 5 As shown, the polysaccharide oil-resistant lightweight packaging paper base material prepared in this embodiment has a layered composite structure, which includes a paper base layer and a polysaccharide oil-resistant barrier layer disposed on the surface of the paper base layer from the inside out. The two layers are connected by a chemical anchoring interface area.

[0179] The paper base is made from a mixture of softwood and broadwood pulp fibers, with a basis weight of 40 to... This embodiment is The paper base layer has a hydrophobic cross-linked network distributed on its fiber surface. This hydrophobic cross-linked network is a network product formed by the cross-linking reaction of hydroxyl groups and aziridine groups of cationic modified starch and polyamide polyamine epichlorohydrin resin. This cross-linked network covers the fiber surface, making the fiber surface more hydrophilic (contact angle 25° to...). It transforms into weakly hydrophobic (contact angle 65° to 10°). Simultaneously, it blocks the capillary channels between fibers, forming a pre-barrier structure at the bottom layer. The cross-linked network retains unreacted residual active groups, which are aziridine groups. The density of the paper base layer is 0.6 to... The longitudinal tensile strength is not less than 3.0 kN / m.

[0180] The polysaccharide oil-resistant barrier layer is disposed on the surface of the paper base layer, with a coating amount of 2 to 1. The single-sided dry coating thickness is approximately 0.9 μm. The polysaccharide oil-repellent barrier layer is mainly composed of amino-containing natural polysaccharides, and in one embodiment, the amino-containing natural polysaccharide is chitosan. The polysaccharide oil-repellent barrier layer also includes cellulose nanofibers and sodium alginate, which are compounded in a mass ratio of 5:3:2. The chitosan and sodium alginate form an ionic cross-linked network framework through the electrostatic interaction of amino and carboxyl groups, and the cellulose nanofibers are dispersed in the framework in an in-plane orientation as a reinforcing component. The polysaccharide oil-repellent barrier layer is a continuous, non-porous, dense film structure, and the penetration path of oil molecules in this film layer is extended to approximately 49 times the thickness of the film layer due to the in-plane orientation of the cellulose nanofibers.

[0181] A chemically anchored interface region exists between the paper substrate and the polysaccharide oil-repellent barrier layer. Within this interface region, the amino groups of the chitosan molecular chains in the polysaccharide oil-repellent barrier layer react with the residual aziridine groups of the cross-linked network on the fiber surface of the paper substrate to form carbon-nitrogen covalent bonds, covalently linking the polysaccharide oil-repellent barrier layer to the fiber surface of the paper substrate. This chemical bonding enhances the adhesion between the coating and the paper substrate from the physical adsorption level (wet adhesion grade 0B to 1B) to the covalent bonding level (wet adhesion grade not less than 3B), maintaining the integrity of the interface structure even under grease wetting and wet conditions.

[0182] The oil-resistant barrier mechanism of the polysaccharide oil-resistant lightweight packaging paper-based material is a two-layer synergistic mode: the hydrophobic cross-linked network inside the paper base layer blocks the lateral diffusion and penetration path of oil through the capillary network between fibers, and the surface polysaccharide oil-resistant barrier layer provides a continuous, non-porous physical barrier. The two layers form an integrated structure through chemical anchoring, making their respective functions interlocked: the bottom pre-barrier reduces the density requirement of the surface coating, so that the polysaccharide oil-resistant barrier layer does not need to bear all the barrier pressure independently, and can achieve an oil-resistant performance of Kit value not lower than 8 under low coating conditions.

[0183] The above is a detailed description of the preparation method of this embodiment.

[0184] like Figure 8As shown, this embodiment also provides a preparation system for preparing the polysaccharide oil-resistant lightweight packaging paper base material. The preparation system includes an intra-pulp crosslinking modification module, a paper forming module, a coating liquid preparation module, a surface coating anchoring module, and a drying and curing module arranged sequentially along the material flow direction.

[0185] The in-slurry crosslinking modification module receives the pulp suspension after beating and sequentially completes two sub-processes: the addition and adsorption of cationic modified starch and the addition and crosslinking of wet strength agent. The in-slurry crosslinking modification module includes a starch gelatinization unit, a starch metering addition unit, a stirred reactor, and a wet strength agent metering addition unit. The stirred reactor is equipped with a temperature control device and an online pH detection device to maintain the pulp reaction temperature at 40°C. Within the specified range and with a pH between 7.0 and 8.5. The output of the in-slurry crosslinking modification module is a modified slurry containing a hydrophobic crosslinking network.

[0186] The paper forming module receives the modified pulp, and after dilution, wire forming, pressing and dewatering, and pre-drying, a paper base is obtained. The paper forming module includes a pulp dilution and mixing unit, a headbox, a wire forming unit, a three-roll press unit, and a pre-drying cylinder group. The cylinder surface temperature of the pre-drying cylinder group is set at 80°C to... Increasing distribution. The paper forming module is also equipped with a microparticle retention aid system to improve the first-pass retention rate of fine components in the modified pulp. The output of the paper forming module is basis weight 40 to... The base paper substrate.

[0187] The coating solution preparation module is set up independently of the main papermaking line and is used to prepare a ternary polysaccharide oil-resistant sizing solution. The module includes a chitosan dissolving vessel, a cellulose nanofiber high-shear dispersion unit, a sodium alginate dissolving vessel, a multi-component mixing tank, a pH adjustment unit, and a vacuum degassing unit. The multi-component mixing tank is equipped with a stirring device and a temperature control device to control the degree of ionic cross-linking pre-assembly during the mixing process. The output of the coating solution preparation module is a ternary polysaccharide oil-resistant sizing solution with a total solids content of approximately 2.0 wt%, a pH of approximately 4.5, and a viscosity of 50 to 500 mPa·s.

[0188] The surface coating anchoring module receives the base paper substrate and the ternary polysaccharide oil-resistant sizing solution, completing the transfer of the coating solution to the paper substrate surface and the initial establishment of the chemical anchoring reaction. The surface coating anchoring module includes a sizing press unit, a constant-temperature storage tank, an online coating amount detection unit, and a coating solution circulation and filtration system. The roll gap pressure of the sizing press unit is adjustable within the range of 20 to 60 kN / m, and the machine speed is matched with the paper forming module. The constant-temperature storage tank maintains the coating solution temperature at 40 to... To promote the chemical anchoring reaction, the online coating amount detection unit uses a β-ray basis weight sensor to detect the difference in paper web basis weight before and after coating in real time, and provides feedback to adjust the pressure of the sizing press line, controlling the coating amount fluctuation within 10% of the set value. The output of the surface coating anchoring module is wet coated paper.

[0189] The drying and curing module receives the wet coated paper and completes moisture evaporation, coating densification, and cross-linked network thermal curing through gradient temperature increase drying. The drying and curing module includes an infrared pre-drying unit and a first drying zone drying cylinder assembly (cylinder surface temperature 80°C to...). ), Second drying zone drying cylinder group (cylinder surface temperature 100 to The third drying zone drying cylinder group (cylinder surface temperature 110 to 100°C) The system includes a cooling cylinder assembly and an online moisture content detection unit. The online moisture content detection unit uses a near-infrared moisture sensor to confirm that the final paper web moisture content is within the range of 5% to 7%. The output of the drying and curing module is a finished polysaccharide-based, oil-resistant, lightweight packaging paper material.

[0190] The modules of the preparation system are connected sequentially via slurry pipelines and a paper web transfer system, forming a continuous production line from slurry to finished paper. The coating solution preparation module, as an independent branch line, transports the prepared sizing solution to the constant-temperature storage tank of the surface coating and anchoring module via pipelines.

[0191] The above embodiments are merely preferred embodiments of this application and are not intended to limit the scope of protection of this application. Any modifications, equivalent substitutions, improvements, etc., made by those skilled in the art within the spirit and principles of this application should be included within the scope of protection of this application.

[0192] Furthermore, the functional units in the various embodiments of this application can be integrated into one processing unit, or each unit can exist physically separately, or two or more units can be integrated into one unit. The integrated unit described above can be implemented in hardware.

[0193] The above description is merely a specific embodiment of this application, but the scope of protection of this application is not limited thereto. Any changes or substitutions within the technical scope disclosed in this application should be included within the scope of protection of this application. Therefore, the scope of protection of this application should be determined by the scope of the claims.

Claims

1. A method for preparing a polysaccharide-based, oil-resistant, lightweight packaging paper material, characterized in that, include: Pulp fibers are subjected to intra-pulp crosslinking treatment to form a hydrophobic crosslinking network containing residual active groups on the surface of the pulp fibers, thereby obtaining a modified pulp. The modified slurry is then formed into a paper base. Prepare an oil-resistant coating solution based on amino-containing natural polysaccharides; The oil-resistant coating liquid is applied to the surface of the paper base. The amino groups of the polysaccharide molecules in the oil-resistant coating liquid react with the residual active groups of the cross-linked network on the surface of the paper base fiber to form a chemical anchor, thereby obtaining a polysaccharide oil-resistant lightweight packaging paper base material.

2. The preparation method according to claim 1, characterized in that, The intra-pulp crosslinking treatment includes: sequentially adding cationic modified starch and a wet strength agent to the pulp fiber, wherein the cationic modified starch is adsorbed on the fiber surface to provide polyhydroxy reaction sites, and the wet strength agent contains nitrogen heterocyclic active groups, wherein the nitrogen heterocyclic active groups react with the polyhydroxy reaction sites and cellulose hydroxyl groups to form the hydrophobic crosslinking network.

3. The preparation method according to claim 2, characterized in that, The wet strength agent is a polyamide polyamine epichlorohydrin resin, and the nitrogen heterocyclic active group is a aziridine group.

4. The preparation method according to claim 1, characterized in that, The oil-resistant coating liquid also contains nanocellulose and carboxyl-containing natural polysaccharides. The amino-containing natural polysaccharides and the carboxyl-containing natural polysaccharides form an ionic cross-linked pre-assembled structure through electrostatic interaction between the amino and carboxyl groups.

5. The preparation method according to claim 4, characterized in that, The amino-containing natural polysaccharide is chitosan, the nanocellulose is cellulose nanofibers, and the carboxyl-containing natural polysaccharide is sodium alginate.

6. The preparation method according to claim 1, characterized in that, It also includes a gradient temperature drying and curing process on the coated paper base, so that the hydrophobic crosslinking network is thermally cured and the polysaccharide coating on the surface of the paper base is densified to form a continuous non-porous barrier film.

7. The preparation method according to claim 1, characterized in that, The reaction conditions for the intraslurry crosslinking treatment are: slurry pH value of 7.0 to 8.5, reaction temperature of 40 to 60 degrees Celsius, and stirring time of not less than 15 minutes.

8. A polysaccharide-based, oil-resistant, lightweight packaging paper material, characterized in that, It includes a paper base layer and a polysaccharide oil-resistant barrier layer disposed on the surface of the paper base layer; the fiber surface of the paper base layer is distributed with a hydrophobic cross-linked network containing residual active groups; the polysaccharide oil-resistant barrier layer is mainly composed of amino-containing natural polysaccharides; the amino groups of the polysaccharide molecules in the polysaccharide oil-resistant barrier layer are chemically bonded to the residual active groups of the hydrophobic cross-linked network to form an anchoring connection.

9. The polysaccharide oil-resistant lightweight packaging paper-based material according to claim 8, characterized in that, The hydrophobic crosslinking network is a network product formed by the crosslinking reaction of the hydroxyl groups of cationic modified starch and the aziridine groups of polyamide polyamine epichlorohydrin resin.

10. The polysaccharide oil-resistant lightweight packaging paper-based material according to claim 8, characterized in that, The basis weight of the paper base layer is 40 to 60 grams per square meter, and the coating amount of the polysaccharide oil-resistant barrier layer is 2 to 3 grams per square meter.